Knights of the Black Cross : Hitler's Panzerwaffe and its leaders - Perrett, Bryan (New York : St. Martin's Press, 1986)
The story of the German Armored Corps --the Panzerwaffee--and the evolution of their superlative fighting vehicles.
'That's what I want-that's what I'm going to have!' -- The annihilation concept at work -- Poisoned victories -- Barbarossa -- Taking stock -- Disaster and recovery -- The Aeschylus factor -- Tigers, Panthers and cauldrons -- The Hydra strikes -- Italy and the campaign in the West -- A present for the Fuhrer -- Appendix A: Some aspects of German tank design -- Appendix B: A short history of the Panzer divisions -- Appendix C: Specimen German orders of battle -- Appendix D: Comparative orders of battle of opposing armoured formations.
Includes bibliographical references (pages 253-254) and index.
Keywords: Germany. -- Heer -- Armored troops -- History; Germany. -- Heer; 1939-1945; World War, 1939-1945 -- Tank warfare; History